DRYING OF RESIDUAL GRAINS OF ANNATTO IN A HEAT ACCUMULATOR DRYER COMBINED WITH DRYING IN A SOLAR DRYER - SANTOS, DYEGO DA COSTA; QUEIROZ, ALEXANDRE JOSÉ DE MELO; DE FIGUEIRÊDO, ROSSANA MARIA FEITOSA; DE OLIVEIRA, EMANUEL NETO ALVES (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
This paper is a study of the drying process of residual grains of annatto in a heat accumulator dryer during the night combined with a solar dryer during the day. Different mathematical models were adjusted regarding experimental data for the dryings and for determining the effective diffusivity for all the processes. The grains were divided into two groups; one with oil, reproducing the conditions of the grains after the oily extraction of bixin, and another group without oil. The drying of the annatto grains of during the night was performed with a heat accumulator dryer, which consisted of solar panel systems that heat water, which is transferred to a thermal tank where it is used as a heat source; during the day a solar dryer was used. Residual grains of annatto with an initial moisture at 18 % w.b. were dehydrated until they reached 5 % w.b. Combined drying using a heat accumulator dryer and a solar dryer proved to be effi cient, with samples presenting lower amounts of moisture compared to the control samples. Midilli’s equation was considered the best model to represent the kinetics of drying residual grains of annatto both with and without oil. Grain samples presented effective diffusivity in the order of 10-9 m2 s-1.